Environmental human rights : power, ethics, and law - Hancock, Jan. (Burlington, VT : Ashgate, 2003)
The criterion used in Jan Hancock's study to investigate the existence of environmental human rights is restricted to existing legal human rights stipulations. Is it possible to rectify current environmental problems by adopting the proposals made by the author.
Rationality, Epistemology and Environmental Human Rights -- Structural Power and Environmental Human Rights -- Social Demands for Environmental Human Rights -- The Formal Response to Environmental Human Rights Claims -- The Human Right to an Environment Free from Toxic Pollution -- The Human Right to Natural Resources.
Includes bibliographical references (pages 167-204) and index.
Keywords: Environmental justice; Environmental ethics